2019
DOI: 10.1016/j.conctc.2019.100324
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of lymph node yield and lymph node ratio in patients affected by squamous cell carcinoma of the oral cavity and oropharynx: Study protocol for a prospective, multicenter, observational study

Abstract: BackgroundLymph node involvement is a fundamental prognostic factor in head and neck squamous cell carcinoma (SCC). Lymph node yield (LNY), which is the number of lymph nodes retrieved after neck dissection, and lymph node ratio (LNR), which is the ratio of positive lymph nodes out of the total removed, are measurable indicators that may have the potential to be used as prognostic factors. The present study is designed to define the exact role of LNY and LNR regarding the overall and specific survival of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
26
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 22 publications
(22 reference statements)
1
26
0
1
Order By: Relevance
“…In the literature, the LNR has been considered an additional factor for estimating prognosis ( 66 , 67 ). In our series, we considered the cut-off value of 0.09 on the basis of the meta-analysis of Talmi et al ( 22 ) who identified 28 studies in the literature that addressed the prognostic value of the LNR and reported a range of cut-off values of the LNR associated with prognosis between 0.02 and 0.20, with an average of 0.09.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the LNR has been considered an additional factor for estimating prognosis ( 66 , 67 ). In our series, we considered the cut-off value of 0.09 on the basis of the meta-analysis of Talmi et al ( 22 ) who identified 28 studies in the literature that addressed the prognostic value of the LNR and reported a range of cut-off values of the LNR associated with prognosis between 0.02 and 0.20, with an average of 0.09.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in patients with a larger burden of regional disease, it may be more beneficial to avoid a chyle leak and proceed without delay to adjuvant therapy than to risk a complication with a deep level‐4 neck dissection. Regardless, the implications of nodal yield on recurrence and survival in HPV‐associated OPSCC should be incorporated into future clinical trial development …”
Section: Discussionmentioning
confidence: 99%
“…Regardless, the implications of nodal yield on recurrence and survival in HPV-associated OPSCC should be incorporated into future clinical trial development. 20…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7] The role of lymph node density or lymph node ratio, defined as the ratio between the total number of positive lymph nodes by the total number of dissected nodes has also been reported. [8][9][10][11][12][13] Many studies have also used these parameters in combination with other nodal characteristics, such as ENE. 3,5,6,13 Our primary goal was to evaluate the role of individual nodal characteristics and their interaction with host characteristics in prognosis of OSCC patients.…”
mentioning
confidence: 99%
“…Lymph node density or lymph node ratio, defined as the ratio between the number of positive lymph nodes and the number of dissected lymph nodes is one such stratifier that has been reported by several authors including our group. [8][9][10][11][12] A major criticism of this parameter has been that it may not be truly predictive of cancer behavior because its value is subject to the surgeons' technical expertize T A B L E 2 Pathologic lymph node characteristics for patients with pathological metastatic lymph nodes (pN+) and comparison of the characteristics based on neutrophil-to-lymphocyte ratio (NLR) values and also to the degree of histopathologic scrutiny of the neck dissection specimen. In the current study we analyzed if lymph node ratio would stratify our patients better, and after carrying out an RPA for lymph node ratio, we did confirm that the classification based on this parameter was accurate ( Figure S3) but the hazard discrimination was poorer than the one obtained using the groups based on number of positive lymph nodes and MLR (0.655 vs. 0.681).…”
mentioning
confidence: 99%